Green managament and its application in the hotel industry - Zapadlo, Kateřina (2017)
The thesis deals with the issue of green management and its application into a hotel. Its purpose is to analyse a selected accommodation facility and to propose a new ecological element application based on the results of the analysis. The thesis also describes a situation among Czech and European ecohotels. There is also a chapter about the motivation of clients making a reservation in a ecohotel.